A population‐based study of long‐term outcome in treated chronic inflammatory demyelinating polyneuropathy. Issue 3 (1st January 2020) - Al‐Zuhairy, Ali; Sindrup, Søren H.; Andersen, Henning; Jakobsen, Johannes
Abstract: Introduction: The effect of long‐lasting immune‐modulating therapy was studied in patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: A population‐based, cross‐sectional study of treated patients referred to the Danish health‐care system between 1985 and 2006. Results: The 51 participating patients had a median disease duration of 16 (interquartile range, 14–21) years. Twenty‐seven patients (53%) had discontinued therapy and 46 walked independently. Disability and isokinetic strength were impaired by 17% and 20%, respectively, as compared with matched control subjects. For a few patients long‐term CIDP was associated with severe morbidity (6%) and even mortality (1%). Prolongation of time until start of therapy was associated with an increased burden of long‐term disability. Discussion: Long‐term prognosis in treated CIDP is characterized by limited disability in the majority of patients. Disability is related to delay of therapy. Therefore, more attention should be given to early treatment start in CIDP.